2005
DOI: 10.1366/0003702054411607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser-Induced Crater Depth in Laser-Induced Breakdown Spectroscopy Emission Features

Abstract: The influence of crater depth on plasma properties and laser-induced breakdown spectroscopy (LIBS) emission has been evaluated. Laser-induced plasmas were generated at the surface and at the bottom of different craters in a copper sample. Plasmas produced at the sample surface and at the bottom of the craters were spatially and temporally resolved. LIBS emission, temperature, and electronic number density of the plasmas were evaluated. It is shown that the confinement effect produced by the craters enhances th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 40 publications
0
44
0
3
Order By: Relevance
“…Also, the sample composition and surface condition may also affect LIBS spectra. For example, craters at the ablation site may have a significant effect on the LIBS intensity [4244]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the sample composition and surface condition may also affect LIBS spectra. For example, craters at the ablation site may have a significant effect on the LIBS intensity [4244]. …”
Section: Discussionmentioning
confidence: 99%
“…Of course continuous ablation at the same location will lead to deep craters and these craters will affect LIBS intensity. Some studies have shown that LIBS in a confined location, for example ablation craters, has a significant effect on the signal intensity [4244]. Dreyer et al .…”
Section: Influence Of Pressurementioning
confidence: 99%
“…Corsi et al created two different crater depths (1 mm in diameter, and 1 mm and 1.5 mm in depth) with a drill on a copper sample. It was shown that the confinement effect produced by the craters enhances the LIBS signal [22]. Shen et al used a series of cylindrical pipes with different diameters to confine the plasma and showed that the maximum signal enhancement factor was about 9 [23].…”
Section: Introductionmentioning
confidence: 99%
“…Corsi et al reported that the plasmas created within the craters were confined by the crater walls. [8] The spatial-confinement effects were clearly observed by using a pair of parallel Al walls in our previous work. [9] In this work, the aim was to study the cylindrical confinement within a round pipe.…”
Section: Introductionmentioning
confidence: 73%